Laminated structure, magnetoresistance element using same, and method for manufacturing laminated structure
Patent Information
- Application Number
- JP2021555969
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-24
- Filing Date
- 2020-10-21
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-10-21
AI Technical Summary
【0015】 本発明は、高いスピン偏極率と、低い電気抵抗を両立させた積層構造及びその製造方法を提供することができる。また、本発明の積層構造を適用した磁気抵抗素子は、次世代の磁気メモリに必要とされる高い磁気抵抗比と、低い面積抵抗で、高密度の記録を実現することができる。
Smart Images

Figure 0007639246000001 
Figure 0007639246000002 
Figure 0007639246000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated structure, a magnetoresistive element using the same, and a method for manufacturing the laminated structure, and in particular to a laminate of a Heusler alloy and graphene. [Background technology]
[0002] With the development of the information society, there is a demand for further improvement in the recording density of magnetic memories. Current magnetic memories use magnetic tunnel junction (MTJ) elements, which have a relatively high magnetoresistance ratio.
[0003] On the other hand, graphene is considered a promising material that paves the way for advanced spintronic devices due to its excellent electrical and physical properties. To date, applications of graphene to current-in-plane (CIP) magnetoresistance elements that handle in-plane spin transport in graphene channels have been studied. In recent years, the development of current-perpendicular-to-plane (CPP) magnetoresistance elements that use graphene as a spacer layer or tunnel barrier layer material has attracted attention. Graphene-based current-perpendicular-to-plane magnetoresistance elements exhibit low electrical resistance and large magnetoresistance effect, and are expected to pave the way for next-generation high-speed and low-power storage and memory technologies (see, for example, Non-Patent Document 1).
[0004] A method has been proposed for improving the spin injection characteristics of graphene by inserting Cu with a thickness of one to several atomic layers into the magnetic metal when graphene is grown on the surface of a magnetic metal such as nickel (Ni) or cobalt (Co) (see, for example, Non-Patent Document 1). A method has also been proposed for precisely controlling the number of graphene layers by controlling the growth atmosphere when graphene is grown on nickel by chemical vapor deposition (CVD) (see, for example, Non-Patent Document 2).
[0005] An example of the material for the ferromagnetic layer of the MTJ element is a Heusler alloy, and an example of the electrode material is graphene (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2016-177689 [Non-patent literature]
[0007] [Non-Patent Document 1] Karpan et al, Phys. Rev. Lett. 99, 176602 (2007) [Non-Patent Document 2] Entani et al, J. Appl. Phys. 6, 064324 (2012) [Non-Patent Document 3] Entani et al, Carbon 61, 134 (2013) [Non-Patent Document 4] Li et al, Appl. Phys. Lett. 103, 042405 (2013) [Non-Patent Document 5] Liu et al, Sci. Rep. 5, 11911 (2015) Summary of the Invention [Problem to be solved by the invention]
[0008] In a typical MTJ element, an insulating layer made of an insulating material is used as the spacer layer or tunnel barrier layer, resulting in high electrical resistance. When attempting to reduce electrical resistance by thinning the insulating layer, the quality of the oxide that forms the insulating layer and the uniformity of its thickness deteriorate, resulting in a lower magnetoresistance ratio. Due to this trade-off, existing MTJ elements are unable to match the high magnetoresistance ratio, which reflects the spin polarization rate of electrons, and the magnitude of the electrical resistance or sheet resistance when a spin-polarized current flows, to the range required for next-generation magnetic memories.
[0009] In Non-Patent Document 1, a heterostructure of a magnetic metal and graphene exerts a spin filtering effect, but the electronic structure of the graphene changes significantly due to the chemical interaction between the graphene and the ferromagnet at the interface. The change in the electronic structure of graphene, that is, the destruction of the Dirac cone structure (for example, Non-Patent Document 3), leads to a decrease in the filtering efficiency and the magnetoresistance ratio.
[0010] An object of the present invention is to provide a laminated structure that achieves both high spin polarization and low electrical resistance, a magnetoresistive element utilizing the same, and a method for manufacturing the laminated structure. [Means for solving the problem]
[0011] The embodiment disclosed below realizes lamination of a Heusler alloy, which has the highest spin polarization rate among known substances, and graphene, which has the weakest spin-orbit interaction among known substances and has low electrical resistance.
[0012] In a first aspect of the disclosure, the laminate structure comprises: Heusler alloys and graphene in direct contact with the Heusler alloy at a surface of the Heusler alloy; has.
[0013] In a second aspect of the disclosure, the laminate structure comprises: a first Heusler alloy layer; and a second Heusler alloy layer; and a graphene layer disposed between the first Heusler alloy layer and the second Heusler alloy layer; has.
[0014] In a third aspect of the disclosure, a method for producing a laminate structure includes: A thin film of a Heusler alloy is formed on a substrate under vacuum. While maintaining the vacuum, graphene is grown on the surface of the thin film of the Heusler alloy. Effect of the Invention
[0015] The present invention provides a laminated structure that achieves both high spin polarization and low electrical resistance, and a manufacturing method thereof. Furthermore, a magnetoresistance element to which the laminated structure of the present invention is applied can achieve high-density recording with a high magnetoresistance ratio and low area resistance, which are required for next-generation magnetic memories. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a schematic diagram showing a cross section of a laminated structure according to an embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing a cross-sectional view of a graphene / Heusler alloy layer structure. [Diagram 3] 1 is a flowchart of a method for manufacturing a graphene / Heusler alloy stacked structure according to an embodiment. [Figure 4A] Optical microscope images showing the growth of graphene on a Heusler alloy (a thin film of CFGG) as a function of exposure (amount of graphene source gas supplied). [Figure 4B] Optical microscope images showing the growth of graphene on a Heusler alloy (a thin film of CFGG) as a function of exposure (amount of graphene source gas supplied). [Diagram 5] 1 is a Raman spectrum of a laminated structure according to an embodiment. [Figure 6A] 1 is a reflection high energy electron diffraction (RHEED) image of a layered structure of an embodiment. [Figure 6B]6B is a RHEED image of the layered structure of the embodiment taken from an angle different from that of FIG. 6A. [Figure 7A] FIG. 13 is a diagram showing the depth dependence of the magnetic moment of a constituent element (Co) of a Heusler alloy (CFGG thin film) in a laminate structure of an embodiment, based on the surface of the laminate structure (position of graphene). [Figure 7B] FIG. 1 is a diagram showing the depth dependence from the surface (position of graphene) of the magnetic moment of a constituent element (Fe) of a Heusler alloy (CFGG thin film) in a stacked structure of an embodiment. [Figure 8] This is a graph showing the spin polarization of the Heusler alloy (CFGG thin film) at various depths from the graphene on the surface of the stacked structure. [Figure 9] FIG. 4 is a schematic diagram of a laminated structure according to another embodiment. [Figure 10] FIG. 9 is a schematic diagram of a magnetoresistance element using the laminated structure of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] In the embodiment, a stacked structure is realized in which the Heusler alloy and graphene are in direct contact with each other. The Heusler alloy has a high spin polarization. The graphene has a uniform thickness, low electrical resistance, and low spin-orbit interaction, which is a factor that causes disorder in the spin direction.
[0018] The surface of a Heusler alloy is easily oxidized, and thus far, no examples of directly growing graphene on the surface of a Heusler alloy have been reported. The above-mentioned patent documents describe graphene on a ferromagnetic layer as an example of an electrode material, but do not mention a specific method for forming graphene. If graphene is to be disposed on a ferromagnetic layer using a Heusler alloy, a transfer method will be used.
[0019] In contrast, in an embodiment, graphene having a thickness of one atomic layer (i.e., monolayer) or multiple atomic layers (i.e., multilayer) is grown directly on the surface of the Heusler alloy to realize a layered structure with a high magnetoresistance ratio and low area resistance.
[0020] <Graphene / Heusler alloy bilayer structure> 1 is a schematic diagram showing a cross section of a layered structure 10 of an embodiment. A layer of graphene 12 is disposed on a surface of a Heusler alloy 11, the layer being in direct contact with the Heusler alloy 11. In this specification and claims, when the Heusler alloy 11 and the graphene 12 are said to be in "direct contact," this means that the Heusler alloy 11 and the graphene 12 are in physical contact with each other without the presence of an oxide or the like at the interface between the graphene 12 and the Heusler alloy 11.
[0021] In other words, graphene 12 is a reaction product between Heusler alloy 11 and carbon, and is formed directly on the surface of Heusler alloy 11. Graphene 12 contained in stacked structure 10 of the embodiment is fundamentally different from a graphene layer arranged on the surface of Heusler alloy 11 by a transfer method. When a graphene layer is arranged on the surface of Heusler alloy 11 by a transfer method, an oxide film is inevitably present at the interface.
[0022] In the laminate structure 10 of the embodiment, since no oxide or the like is present between the Heusler alloy 11 and the graphene 12, low electrical resistance and high magnetoresistance ratio are achieved.
[0023] Due to their half-metallic nature, Heusler alloys have the highest spin polarization of conduction electrons among all known substances, reaching a value of nearly 100% at room temperature. In other words, Heusler alloys have excellent ability to align the direction of electron spins.
[0024] In one embodiment, a full Heusler alloy represented by the general formula X2YZ is used among the Heusler alloys. Here, X and Y are transition metal elements, and Z is a group 13-15 element. The full Heusler alloy has a crystal structure called an L21 structure in which four face-centered cubic (fcc) lattices are nested. The full Heusler alloy is preferable because it has a high Curie temperature and many systems that exhibit half-metal properties, but a half Heusler alloy represented by the general formula XYZ may also be used.
[0025] Half metals have a metallic state and a semiconductor state with a band gap depending on the spin direction. As a result, at the Fermi level, the spins of electrons are completely aligned in one direction, resulting in a spin polarization rate of 100%.
[0026] As X, Co, Ni, Ru, Rh, etc. can be used. As an example, a Heusler alloy represented by Co2YZ with a high Curie temperature and spin polarization rate is used. Y is selected from V, Cr, Ti, Mn, Fe, combinations thereof, etc. Z is selected from Al, Si, Ga, Ge, Sn, combinations thereof, etc.
[0027] Specific combinations of Co2YZ include Co2VAl, Co2VSi, Co2VGa, Co2VGe, Co2VSn, Co2CrAl, Co2CrSi, Co2CrGa, Co2CrGe, Co2CrSn, Co2TiAl, Co2TiSi, Co2TiGa, Co2TiGe, Co2TiSn, Co2MnAl, Co2MnSi, Co2MnGa, Co2MnGe, Co2MnSn, Co2FeAl, Co2FeSi, Co2FeGa, Co2FeGe, Co2FeSn, Co2FeGe 1-x Ga x , Co2MnGe 1-x Ga x , Co2FeAl 1-x Si x , Co2Fe 1-x Mn x Si, Co2Mn 1-x Fe x Ge, Co2Fe 1-x Ti x Si(0 < x < 1), etc. can be mentioned.
[0028] Graphene 12 is a sheet-like substance in which carbon (C) atoms are bonded in a honeycomb pattern. The relationship between the energy and momentum of electrons in the conduction band and valence band of graphene can be simulated by symmetric cones (Dirac cones) with vertices touching at the Dirac points (K points or K' points in wave number space). Since graphene has no bandgap, it has low electrical resistance, and due to having Dirac cones, it has high carrier mobility. Also, among known substances, it has the smallest spin-orbit interaction and spin scattering is less likely to occur. That is, graphene is excellent in the performance of transmitting while maintaining the spin direction.
[0029] Due to these characteristics, it is possible to use graphene as a low-resistance spacer layer or a tunnel barrier layer of a planar direct current type magnetoresistive element.
[0030] Figure 2 is a schematic view of the laminated structure of graphene / Heusler alloy seen from the cross-sectional direction. When the (001)-oriented L21 structure Heusler alloy 11 is viewed from the side (cross-sectional direction), the layers where X atoms 11a are located (L1, L3, L5,...) and the layers where Y atoms 11b and Z atoms 11c are located (L2, L4,...) are alternately positioned. There may also be a case where the order of the layer where X atoms 11a are located and the layers where Y atoms 11b and Z atoms 11c are located is reversed, that is, when X atoms 11a are located in L2, L4,... and Y atoms 11b and Z atoms 11c are located in L1, L3, L5,....
[0031] Co2FeGe 1-x Ga x When using (0 < x < 1), for example, Co is located in the odd-numbered layers (L1, L3, L5,...) and Fe, Ge, and Ga are located in the even-numbered layers (L2, L4,...).
[0032] In graphene 12, a hexagonal lattice is formed by the bonding of C atoms 12a. The s orbital of C atom 12a and two p orbitals are hybridized. One electron of the 2s orbital is excited to the 2p orbital, and in the plane, the s orbital, px orbital, and py orbital are oriented at an angle of 120° to each other. Graphene 12 with such a structure has a strong bonding force in the in-plane direction.
[0033] Generally, when growing graphene on magnetic metals such as Ni and Co by CVD, a source gas containing hydrocarbons is supplied to the surface of the magnetic metal. However, unlike magnetic metals with simple structures, Heusler alloys contain many types of elements and have complex crystal structures. For this reason, there have been no reports of a layered structure in which graphene is grown directly on the surface of a Heusler alloy.
[0034] The surface of a Heusler alloy is easily oxidized. Graphene cannot be grown on the surface of an oxidized Heusler alloy by the CVD method. Although it is possible to place graphene on the surface of an oxidized Heusler alloy by using a transfer method, in this case a layer of metal oxide remains at the interface between the Heusler alloy and the graphene layer. If a layered structure with a metal oxide is applied to an MTJ element, the low electrical resistance characteristic of graphene is lost.
[0035] In the embodiment, a thin film of a Heusler alloy and graphene are successively grown by sputtering and CVD while maintaining a high degree of vacuum.
[0036] 3 is a flow chart of a method for manufacturing a graphene / Heusler alloy laminated structure according to an embodiment. First, a thin film of a Heusler alloy is grown in a vacuum (S11). In this specification and claims, the terms "under vacuum" and "in a vacuum" refer to a temperature of 1×10 -4 It means a high vacuum state of less than 1 Pa. For example, the degree of vacuum is 1×10 -5 Pa or less, more preferably 1×10 -6 A thin film of a Heusler alloy is formed on a single crystal MgO (001) substrate by a sputtering method such as magnetron sputtering in a vacuum chamber at or below Pa. The thickness of the Heusler alloy thin film is, for example, 1 to 200 nm, and preferably 10 to 100 nm.
[0037] In this embodiment, a numerical range described using "to" includes the lower limit value itself and the upper limit value itself before and after "to". As a material for a substrate for forming a Heusler alloy thin film, SiO2 may be used instead of the above-mentioned MgO. A thin film of an alloy such as Ru, Ag, Cr, Ta, or NiAl may be formed on a substrate, and the Heusler alloy thin film may be formed on the thin film.
[0038] If the thickness of the Heusler alloy thin film is less than 1 nm, for example, the properties of the Heusler alloy, such as ferromagnetism and high spin polarization, are not fully exhibited, and if the thickness of the Heusler alloy thin film exceeds 200 nm, it becomes difficult to reduce the size and thickness of an element to which the layered structure 10 is applied.
[0039] As an example, the stoichiometric ratio is Co2FeGe 0.5 Ga 0.5 Using the base material or target of Co2FeGe 0.5 Ga 0.5 A thin film of CFGG (hereafter abbreviated as "CFGG") is formed on a single crystal MgO (001) substrate. Of all the Heusler alloys, CFGG has the highest spin polarization. The Ar gas pressure is 0.5 Pa to 1 Pa, the substrate temperature is 500°C to 650°C, and the input power is 10 to 60 W. A single crystal CFGG thin film with a crystal orientation aligned to (001) is formed by magnetron sputtering.
[0040] Next, the CFGG thin film is moved to a second vacuum chamber while being kept in a vacuum (S12). In order to maintain a high vacuum state, a film formation apparatus in which multiple vacuum chambers are connected in series in a sealed state may be used.
[0041] Next, graphene is grown directly on the CFGG thin film by CVD in a second vacuum chamber. The vacuum level in the second vacuum chamber is 1×10 -5 Pa or less, more preferably 1×10 -6 Pa or less.
[0042] As the raw material gas, a gas containing a hydrocarbon that is the raw material of graphene, such as methane (CH4), ethylene (C2H4), acetylene (C2H2), benzene (C6H6), toluene (C6H5CH3), or methanol (CH3OH), is supplied to the surface of the thin film of the Heusler alloy (S13). The pressure of the raw material gas is 1 Pa or less.
[0043] While supplying the raw material gas, carbon and CFGG are reacted with each other (S14) in a state where the temperature of the substrate is controlled in the range of 500 to 650°C, and a graphene film is formed as a reaction product on the CFGG thin film (S15). If the substrate temperature exceeds 650°C, the flatness of the CFGG thin film is impaired, and the uniformity of the grown graphene is impaired. If the substrate temperature is less than 500°C, the CFGG thin film does not exhibit the L21 structure required for the expression of half-metallic properties. In other words, the substrate temperature of 500°C is the lower limit temperature for the transformation of the Heusler alloy CFGG into the L21 structure required for the expression of half-metallic properties.
[0044] Into the second vacuum chamber where the CFGG thin film was placed (on the CFGG thin film), the source gas was introduced at a concentration of 1×10 4 L~1×10 5 L(1L(Langmuir)=1.33×10 -4 By supplying the vacuum at a pressure of 10 Pa·sec, single-layer graphene is formed on the CFGG thin film with 100% coverage. By maintaining the vacuum in this way and performing CVD on the single-crystalline CFGG thin film, high-quality single-layer graphene is obtained with complete coverage.
[0045] The manufacturing method shown in Figure 3 makes it possible to form graphene directly on a thin film of a Heusler alloy without the presence of oxides or other materials at the interface. In addition, because graphene is grown on the surface of a thin Heusler alloy film by CVD while maintaining a vacuum, it is possible to form a large-area graphene / Heusler alloy laminated structure on a substrate of any shape or size, such as a wafer. Furthermore, because the surface of the graphene / Heusler alloy laminated structure created in this way is completely covered with stable graphene, the Heusler alloy does not oxidize even when taken out into the air. These facts suggest the ease of application to large-scale integrated devices and use as a practical material.
[0046] <Characteristics of graphene / CFGG stacked structure> Figure 4A shows an optical microscope image of a partially graphene-coated Heusler alloy surface. The bright contrast indicates the areas covered by graphene. The dark contrast indicates the areas of CFGG that are not covered by graphene. This contrast is not observed in the as-formed graphene / CFGG stack. By heating the graphene / CFGG stack in air or in an oxygen atmosphere, only the areas that are not covered by graphene and where the CFGG thin film is exposed at the surface oxidize and change color, resulting in the contrast.
[0047] Figure 4B is an optical microscope image of the surface of a CFGG thin film completely covered with graphene. The growth rate of graphene in the CVD method varies greatly depending on the thickness of the graphene. By appropriately controlling the supply conditions of the raw material gas, including the supply amount (exposure amount) of the raw material gas that is the source of graphene, it is possible to form uniform single-layer graphene with a coverage rate of 100%. Furthermore, by increasing the exposure amount, it is also possible to form multilayer graphene with a thickness of several layers.
[0048] 5 is a Raman spectrum of the laminated structure 10 of the embodiment. The Raman peaks specific to graphene (D band, G band, and 2D band) appear in the spectrum. The intensity of the D band caused by defects is smaller than that of the G band, which indicates the high crystal quality of the single-layer graphene formed on CFGG.
[0049] The areal intensity ratio of the 2D band to the G band (I(2D) / I(G)) is about 1.1, indicating that the monolayer graphene experiences the charge doping effect arising from the CFGG.
[0050] 6A and 6B are RHEED images of the layered structure 10 of the embodiment. Fig. 6A is an image obtained from an electron beam incident at an angle parallel to the
[0110] direction of the MgO substrate, and Fig. 6B is an image obtained from an electron beam incident at an angle parallel to the
[0100] direction of the MgO substrate.
[0051] In Figures 6A and 6B, the downward arrows indicate the reflection patterns from CFGG, and the upward arrows indicate the diffraction patterns from single-layer graphene (labeled "SLG" in the figures). The sharp striped reflection patterns obtained from both graphene and CFGG confirm that graphene is grown directly on the CFGG thin film and that the interface between CFGG and graphene is atomically flat.
[0052] If an oxide film or the like is present between the Heusler alloy and graphene, the RHEED diffraction pattern from the Heusler alloy is not observed. The fact that there is no oxide film or the like at the interface between the Heusler alloy and graphene can be easily seen by examining the RHEED diffraction pattern of the layered structure.
[0053] In Fig. 6B, the gray downward arrows of CFGG are 1 / 2-order superlattice diffractions originating from the L21 crystal phase of CFGG, indicating that the crystal structure related to the half-metallicity of CFGG is well preserved even near the interface between graphene and CFGG.
[0054] From the RHEED images in Figures 6A and 6B, the lattice constant of CFGG near the interface with graphene is estimated to be 0.57 nm, which is consistent with the lattice constant of the entire CFGG thin film evaluated by X-ray diffraction (XRD) (0.574 nm).
[0055] In Fig. 6B, the dashed upward arrows of the SLG indicate the overlap of the diffraction lines of graphene and CFGG. Unlike the diffraction pattern of CFGG, the diffraction pattern and intensity from graphene do not show a clear dependence on the incident azimuth angle, indicating a random in-plane orientation of the hexagonal lattice of graphene with respect to the (001) plane of CFGG.
[0056] The randomness of the in-plane orientation of the graphene crystals (i.e., polycrystalline nature) reflects the weak bonding between graphene and the CFGG(001) surface, which is due to weak van der Waals interactions and therefore has less adverse effect on the electronic state of graphene (high electron mobility and spin transport properties explained by the zero band gap and Dirac cone).
[0057] The lattice constant of the monolayer graphene grown in the embodiment is estimated to be 0.25 nm from RHEED images, which is consistent with the in-plane lattice constant of graphite (0.246 nm).
[0058] In this way, by maintaining the vacuum and growing graphene on the CFGG thin film by CVD, it is possible to grow high-quality graphene with 100% coverage.
[0059] <Magnetic properties at the graphene / CFGG interface> 7A and 7B show the depth dependence of the magnetic moment of the CFGG thin film in the layered structure 10 of the embodiment. Fig. 7A shows the depth dependence of the magnetic moment of Co atoms forming CFGG, and Fig. 7B shows the depth dependence of the magnetic moment of Fe atoms. The magnetic moment is an index of the strength of magnetism.
[0060] The magnetic properties of the graphene–CFGG interface region can be analyzed by Depth-Resolved X-ray Magnetic Circular Dichroism (DR-XMCD) spectroscopy, which is the difference in X-ray absorption intensity measured with left- and right-handed circularly polarized light while the sample is magnetized.
[0061] The magnetic moments of Co and Fe at each depth are the sum of the spin and orbital magnetic moments. The gray region is the interface region where the CFGG thin film contacts the graphene. The numbers on the horizontal axis represent the depth relative to the graphene at the surface of the stacked structure. For both Co and Fe, the magnitude of the magnetic moment is almost the same as the magnitude of the magnetic moment inside the thin film, shown by the dashed line, from the depth of 1.7 nm, which is far from the interface, to the interface with graphene.
[0062] Although the magnetic moment is slightly reduced in the region of 0.5 nm to 0.7 nm in the depth direction, the change in the magnetic moment is within 10% of the magnetic moment inside the thin film.
[0063] In the layered structure 10, the magnitude of the magnetic moment is maintained throughout the graphene / CFGG interface even within the thin film (i.e., the magnetism is homogenized in the film thickness direction), which is a major difference from conventional graphene / magnetic metal heterostructures described, for example, in Non-Patent Document 5.
[0064] Figure 8 shows the spin polarization of the CFGG thin film at each depth based on the graphene at the surface of the stacked structure. The spin polarization in Figure 8 is a predicted value obtained by theoretical calculation based on the experimental results using depth-resolved X-ray magnetic circular dichroism spectroscopy and other methods. The horizontal axis is the electron energy (eV), and the vertical axis is the spin polarization (%). 0 eV on the horizontal axis indicates the Fermi level. 100% spin polarization is achieved at depths of 0.33 nm (3.3 Å), 0.47 nm (4.7 Å), 0.62 nm (6.2 Å), and 0.76 nm (7.6 Å). The results in Figure 8 are for a sample whose outermost layer in contact with graphene at the interface is made of Co atoms, and are calculated based on the density of states of the electron orbitals in the interface region. However, good spin polarization can be obtained up to the interface even for samples whose outermost layer is made of Fe atoms, Ge atoms, and Ga atoms.
[0065] <Three-layer structure of Heusler alloy / graphene / Heusler alloy> 9 is a schematic diagram of a laminated structure 20 according to another embodiment. The laminated structure 20 has a three-layer structure of Heusler alloy / graphene / Heusler alloy. A single or multiple layers of graphene 12 are located between a Heusler alloy 11 and a Heusler alloy 21 in the stacking direction.
[0066] In the stacked structure 20, a graphene layer is sandwiched between two Heusler alloy layers, thereby achieving both high spin polarization and low electrical resistance. In the stacked direction, at least the Heusler alloy 11 and the graphene 12 are in direct contact with each other. The graphene 12 and the Heusler alloy 21 may also be in direct contact with each other.
[0067] When Heusler alloy 21 is grown directly on graphene 12, the sample is moved to a Heusler alloy deposition chamber while still in vacuum after step S15 in Fig. 3. When a thin film of Heusler alloy 21 with the same composition as Heusler alloy 11 is to be formed, the transport mechanism is driven to return the sample to the initial chamber. When a thin film of Heusler alloy 21 with a different composition from Heusler alloy 11 is to be formed, another deposition chamber is connected in series while still in vacuum.
[0068] The three-layered laminated structure 20 in FIG. 9 can be applied to a magnetoresistance element together with the two-layered laminated structure 10. In this case, the graphene 12 functions as a spacer layer or a tunnel barrier layer. Unlike conventional element structures in which a tunnel barrier layer is formed from an insulating material, graphene has low electrical resistance and small spin-orbit coupling. In addition, the good magnetic properties and half-metallic properties of the Heusler alloy can be maintained at the graphene / Heusler alloy interface. For these reasons, when the laminated structure 20 is applied to a magnetoresistance element, it is possible to achieve both low sheet resistance and high magnetoresistance ratio.
[0069] <Application to magnetoresistance elements> 10 is a schematic diagram of a magnetoresistance element 100 using the laminated structure 30 of the embodiment. A first conductive layer 41, the laminated structure 30, an antiferromagnetic layer 43, and a second conductive layer 42 are laminated on a substrate 45 in this order.
[0070] In the stacked structure 30, a first Heusler alloy layer 31, a graphene layer 32, and a second Heusler alloy layer 33 are stacked in this order. The graphene layer 32 is sandwiched between the first Heusler alloy layer 31 and the second Heusler alloy layer 33, which are ferromagnetic materials, and serves as a spacer layer or a tunnel barrier layer.
[0071] In more detail, the spacer layer is, for example, a layer sandwiched between a pair of ferromagnetic layers, and a current flows between the pair of ferromagnetic layers via the spacer layer body (electrons move inside the spacer layer). On the other hand, the tunnel barrier layer is, for example, a layer sandwiched between a pair of ferromagnetic layers, and electrons (current) move between the pair of ferromagnetic layers by the tunnel effect without passing through the tunnel barrier layer body. Here, the graphene layer 32 illustrated in FIG. 10 can function as both the spacer layer and the tunnel barrier layer, depending on, for example, the combination of the thickness of the graphene layer 32 and the materials (magnetic materials) constituting the first and second Heusler alloy layers 31 and 33.
[0072] The first Heusler alloy layer 31 is, for example, a free layer or a recording layer in which the direction of magnetization changes, as shown by a bidirectional arrow in Fig. 10. The second Heusler alloy layer 33 is a pinned layer or a reference layer in which the direction of magnetization is fixed, as shown by a unidirectional arrow in Fig. 10.
[0073] The antiferromagnetic layer 43 has antiferromagnetic properties in which the magnetic moments of the atoms forming the crystals are arranged to cancel each other out. The antiferromagnetic layer 43 does not have spontaneous magnetization as a whole.
[0074] The direction of magnetization of the second Heusler alloy layer 33 in contact with the antiferromagnetic layer 43 is exchange-coupled with the antiferromagnetic layer 43, and is difficult to orient in the direction of the applied magnetic field in a practical magnetic field. On the other hand, the magnetization of the first Heusler alloy layer 31 located on the opposite side to the second Heusler alloy layer 33 across the graphene layer 32, which is a spacer layer, changes depending on the direction of the current or magnetic field.
[0075] The first conductive layer 41 and the second conductive layer 42 function as electrodes. By switching the direction of the current applied between the first conductive layer 41 and the second conductive layer 42, the direction of magnetization of the first Heusler alloy layer 31 is switched, making it possible to record digital information "0" and "1".
[0076] Information corresponding to "0" and "1" is read by reading the change in electrical resistance due to the relative magnetization direction (parallel or anti-parallel) between the first Heusler alloy layer 31 and the second Heusler alloy layer 33. When the magnetization direction of the first Heusler alloy layer 31 and the magnetization direction of the second Heusler alloy layer 33 are aligned (parallel), the resistance is small. When the magnetization direction of the first Heusler alloy layer 31 and the magnetization direction of the second Heusler alloy layer 33 are opposite (anti-parallel), the resistance is large.
[0077] By using the stacked structure 30 of the embodiment, a high spin polarization rate is maintained even at the interface between the Heusler alloy layer and the graphene (see FIG. 8). In the graphene layer 32 that functions as a spacer layer or a tunnel barrier layer, a unique electronic state called a Dirac cone is maintained. Since the electron mobility is high and the spin-orbit interaction is small, the spin transfer ability is excellent.
[0078] The area resistance of a magnetoresistance element using graphene as a spacer layer or tunnel barrier layer is 10 -2 Ωμm 2 By changing the thickness of graphene to the range of 1 to 4 atomic layers, the sheet resistance can be increased to the range required for magnetoresistance elements of next-generation high-density magnetic memories (10 -2 ~10 2 Ωμm 2 It is expected that it will be possible to control the
[0079] The magnetoresistance element 100 can be applied to hard disk drives, magnetic random access memories (MRAMs), etc. These magnetic memories use the magnetic properties (spin) of electrons to store a large amount of information in a small amount of data. stomach It can be stored as electricity.
[0080] The present invention is not limited to the above-mentioned examples. The Heusler alloy may be formed by magnetron sputtering, bipolar sputtering, or vacuum deposition. The graphene on the Heusler alloy may be formed by physical vapor deposition (PVD) by depositing carbon clusters such as atomic carbon or fullerenes generated by sputtering or pulsed laser irradiation, as well as by CVD. The film formation conditions of the Heusler alloy can be appropriately changed depending on the composition, film thickness, and the like. As the Heusler alloy, not only the L21 type full-Heusler alloy but also a half-Heusler alloy represented by the general formula XYZ may be used. In this case, too, graphene can be grown directly on the surface of the half-Heusler alloy while maintaining the vacuum. Some half-Heusler alloys also exhibit half-metallic properties and have a higher spin polarization rate than general magnetic metals.
[0081] This application claims priority to U.S. Provisional Patent Application No. 62 / 935,154, filed in the United States on November 14, 2019, and Japanese Patent Application No. 2020-052726, filed in Japan on March 24, 2020, the entire contents of which are incorporated by reference. [Explanation of symbols]
[0082] 10, 20, 30 laminate structure 11, 21 Heusler alloy 12. Graphene 31 First Heusler alloy layer 32 graphene layers 33 Second Heusler alloy layer 41 First conductive layer 42 Second conductive layer 43 Antiferromagnetic layer 45 Substrate 100 Magnetoresistance element
Claims
1. A Heusler alloy having an L2 1 crystal structure, Graphene in direct contact with the Heusler alloy on a surface of the Heusler alloy and having a Dirac cone structure as an electronic structure; A laminated structure having the above structure.
2. 2. The layered structure of claim 1, wherein the graphene is a reaction product of the Heusler alloy and carbon.
3. The laminated structure according to claim 1 or 2, wherein the laminated structure exhibits both diffraction from the graphene and diffraction from the Heusler alloy in reflection high energy electron diffraction at a predetermined angle of incidence.
4. a first Heusler alloy layer; a second Heusler alloy layer; and a graphene layer disposed between the first Heusler alloy layer and the second Heusler alloy layer and having a Dirac cone structure as an electronic structure; having A laminate structure, wherein the graphene layer is in direct contact with at least one of the first Heusler alloy layer and the second Heusler alloy layer, the Heusler alloy layer having an L2 1 crystal structure.
5. The stacked structure of claim 4 , wherein an interface between the graphene layer and the first Heusler alloy layer and an interface between the graphene layer and the second Heusler alloy layer are free of oxide.
6. A laminate structure according to claim 4 or 5, An electrode layer provided on the laminated structure; A magnetoresistive element having
7. forming a thin film of a Heusler alloy on a substrate under vacuum; While maintaining the vacuum, the temperature of the substrate is set to a range of 500° C. or more and 650° C. or less, and graphene is grown on the surface of the thin film of the Heusler alloy. A method for manufacturing a laminate structure.
8. supplying a carbon-containing raw material to a surface of the thin film of the Heusler alloy; reacting the carbon with the Heusler alloy to grow graphene on the surface of the thin film of the Heusler alloy; A method for producing the laminate structure according to claim 7.
9. The method for manufacturing a laminate structure according to claim 7 or 8, wherein the graphene is formed by chemical vapor deposition or physical vapor deposition.
10. forming a thin film of the Heusler alloy in a first vacuum chamber; the substrate on which the Heusler alloy thin film is formed is moved to a second vacuum chamber while maintaining the vacuum; growing the graphene in the second vacuum chamber; A method for producing the laminate structure according to any one of claims 7 to 9.
11. Vacuum degree 1 x 10 -5 forming a thin film of the Heusler alloy in the first vacuum chamber at a pressure of 0.1 Pa or less; A method for producing the laminate structure according to claim 10.
12. Vacuum degree 1 x 10 -5 The graphene is grown in the second vacuum chamber at a pressure of Pa or less. A method for producing the laminate structure according to claim 10 or 11.
Citation Information
Patent Citations
Tunneling magnetoresistive element and its manufacturing method
JP2006319234A
Memory system
JP2016177689A
Integrated circuit having a magnetic tunnel junction device and method
US20090321860A1
Magnetic Field Sensor Using In Situ Solid Source Graphene and Graphene Induced Anti-Ferromagnetic Coupling and Spin Filtering
US20170242083A1
Spin logic with magnetic insulators switched by spin orbit coupling
US20180240964A1